Best Answer

That doesn't factor neatly. Applying the quadratic formula, we find two real solutions:-6 plus or minus 2 times the square root of 2

x = -3.1715728752538097

x = -8.82842712474619

More answers

Are you sure of the signs in the equation?

The discriminant of this quadratic is 122 - 4*1*28 = 32

So the roots are [-12 +/- sqrt(32)]/2 = -6 +/- 2sqrt(2)

So the factorisation is [x+6-2sqrt(2)] * [x+6+2sqrt(2)]

Factor 2x plus 12x plus 28 is (x - 3)(x - 9)

-((x + 2)(x - 14))

(x - 7)(x - 4)

Q: -x2 plus 12x plus 28 factorization?

Write your answer...

Submit

Still have questions?

Continue Learning about Movies & Television

-(x - 14)(x + 2)

(x + 4)(x + 8)

(x + 4)(x + 1)

(x + 13)(2 - x)

x2-3x+2.25 is the same as 4x2-12x+9 and is (2x-3)(2x-3) when factored

Related questions

x2+12x+28Improved Answer:--x2+12x+28 = (-x+14)(x+2) when factored

x2 + 12x + 27 = (x + 9)(x + 3)

-(x - 14)(x + 2)

x + 12x + 20 = (x + 10)(x + 2)

3x(x2 + 2x - 4)

-2x3 + 2x2 + 12x =(-2x) (x2 - x - 6) =(-2x) (x+2) (x-3)

I would do this. Multiply through by -1 -1 ( -X^2 +12X +28 ) = X^2 -12X -28 (X+2)(X-14)

(-2x3 - 2x2 + 12x) = -2x (x2 + x - 6) = -2x (x + 3) (x - 2)

x2+12x+5 = 3 x2+12x+5-3 = 0 x2+12x+2 = 0

x2-12x+36 = (x-6)2

-2x3 + 2x2 + 12x = -2x(x2 - x - 6) = -2x(x2 + 2x - 3x - 6) = -2x[ x(x + 2) - 3(x + 2) ] = -2x(x - 3)(x + 2)

x2 + 12x + 32 = (x + 8)(x + 4)